KEEFEKTIFAN MODEL PEMBELAJARAN TALKING STICK BERBANTU MACROMEDIA FLASH TERHADAP HASIL BELAJAR PADA PEMBELAJARAN TEMATIK SISWA KELAS V SEKOLAH DASAR - Feny Nur Oktaviani; Ali Shodiqin; Ikha Listyarini (Jurnal Guru Kita PGSD, 2019)
Abstract: Effectiveness of Talking Stick Learning Model helped Macromedia Flash on Learning Outcomes in Thematic Learning of Class V Elementary Students. The aim of this research is to find out the learning outcomes of talking stick learning models assisted with Macromedia Flash.This type of research uses quantitative research methods, the research design is true experimental design in the form of pretest posttest control group design. The study population was students of class V of SD Kalicari 01 Semarang in the 2019/2020 school year. Samples taken were 25 VA and VB grade students who used the Probability sampling technique, namely simple random sampling. Data in this study were obtained through interviews, tests, observations, and documentation. Based on the results of calculations using the t test obtained t count = 2.403 with t table = 2.021. Because tcount = 2.403> t table = 2.021, H0 is rejected and Ha is accepted. This means the learning outcomes of thematic learning with learning models talking sticks assisted with macromedia flash are better with learning outcomes with conventional methods in fifth grade elementary school students.Keywords: Talking Stick, Macromedia Flash, Thematic LearningAbstrak: Keefektifan Model Pembelajaran Talking Stick berbantu Macromedia Flash terhadap Hasil Belajar Pada Pembelajaran Tematik Siswa Kelas V Sekolah Dasar. Tujuan yang hendak dicapai dalam penelitian ini adalah untuk mengetahui hasil belajar dengan model pembelajaran talking stick berbantu Macromedia Flash. Jenis penelitian ini menggunakan metode penelitian kuantitatif, dengan rancangan penelitian yaitu true experimental design bentuk pretest posttest control group design. Populasi penelitian adalah siswa kelas V SD Negeri Kalicari 01 Semarang tahun pelajaran 2019/2020. Sampel yang diambil adalah 25 siswa kelas VA dan VB yang menggunakan teknik Probability sampling, yaitu simple random sampling. Data dalam penelitian ini diperoleh melalui wawancara, tes, observasi, dan dokumentasi. Berdasarkan hasil perhitungan dengan menggunakan uji t diperoleh thitung = 2,403 dengan ttabel = 2,021. Karena thitung = 2,403 > ttabel = 2,021 maka H0 ditolak dan Ha diterima. Hal ini berarti hasil belajar pembelajaran tematik dengan model pembelajaran talking stick berbantu macromedia flash lebih baik dengan hasil belajar dengan metode konvensional pada siswa kelas V sekolah dasar. Kata Kunci: Talking Stick, Macromedia Flash, Pembelajaran Tematik.